PENDEKATAN HAK ASASI MANUSIA PADA SISTEM PEMIDANAAN DAN PUTUSAN PERKARA KORUPSI - Ali, Mahrus (Veritas et Justitia, 2020)
This juridical normative and empirical study is conducted with the aim at analyzing the relationship between corruption and human rights violation. Two issues shall be discussed, i.e. what factors inhibits the use of human right approach in corruption cases and what changes can be made to the criminal justice system, especially in relation to the penal judgement. One factor inhibiting the use of a human right approach in handling corruption cases in the perspective of treating corruption as pure criminal act wholly unrelated to violation of human rights.  To rectify this situation and accommodate this human right approach, the author recommends to prioritize and use fine which basic value is social welfare.  Court decision in corruption cases, in addition, should when evaluating elements of crime charges, explicitly describe those rights of the victims which are violated and use this consideration in determining what penal sanction are to be given.